Comparison of blood tonic efficacy and chemical constituents of Kadsura interior A.C. Smith and its closely related species - Jing Xu; Jiushi Liu; Bin Li; Xueping Wei; Yaodong Qi; Bengang Zhang; Haitao Liu; Peigen Xiao (BMC, 2022)
Abstract Background The stems of Kadsura interior A. C. Smith are used as traditional Chinese medicine (TCM) Kadsurae Caulis, with the traditional efficacy of tonifying and invigorating the blood, therefore being favored to treat blood deficiency (BD) widely. However, the stems of K. interior and its closely related species are morphologically similar and they may readily be misused as Kadsurae Caulis, thus likely to exert negative effects on clinical efficacy and clinical medication safety. Methods Firstly, blood tonic efficacies of the stems of K. interior (KIS) and its closely related species were compared using BD mouse model induced by 1-acetyl-2-phenylhydrazine (APH) and cyclophosphamide (CTX). Secondly, the chemical constituents from the stems of K. interior and its closely related species were evaluated and compared using a plant metabolomics approach. Plant metabolomics in this study aims at discovering differential metabolites and comprehensively assessing the chemical constituents by combining state-of-the-art high-resolution UPLC-Q/TOF-MS/MS technique and multivariate data analysis. Finally, based on the pharmacological data and the chemical constituents in UPLC-Q/TOF-MS fingerprints, the potential blood tonic active markers were screened by the spectrum-effect relationship analysis and quantified by UPLC-UV-DAD. Results The ethanol extract of the stems of K. interior significantly increased the levels of hematocrit (HCT), hemoglobin (HGB), and red blood cells (RBC) in BD mice. In addition, it significantly increased the serum levels of interleukin 3 (IL-3), granulocyte-macrophage colony-stimulating factor (GM-CSF), and macrophage-stimulating factor (M-CSF) in BD mice (P < 0.01). The blood tonic efficacy of the stems of K. interior was superior to those of its closely related species, especially at the dose of 200 mg/kg. Six differential compounds in the stems of K. interior were screened out to distinguish it from its closely related species. In combination with the results of the spectrum-effect relationship analysis, heteroclitin D, interiorin C, and heteroclitin G were identified as potential bioactive markers. The contents of heteroclitin D and heteroclitin G in the freeze-dried powder of KIS were 15.90 and 3.74 μg/mg. Conclusions This study illustrated the differences in the blood tonic efficacies and the chemical constituents of the stems of K. interior and its closely related species, and pinpointed the potential bioactive markers of K. interior.